2011
DOI: 10.1586/epr.11.47
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the histone code with quantitative mass spectrometry

Abstract: Histone post-translational modifications (PTMs) comprise one of the most intricate nuclear signaling networks that govern gene expression in a long-term and dynamic fashion. These PTMs are considered to be ‘epigenetic’ or heritable from one cell generation to the next and help establish genomic expression patterns. While much of the analyses of histones have historically been performed using site-specific antibodies, these methods are replete with technical obstacles (i.e., cross-reactivity and epitope occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 112 publications
0
109
0
1
Order By: Relevance
“…Moreover, histone PTMs cross-talk in a synergistic manner to fine-tune gene expression (5). Therefore, quantification of histone PTMs has become a high priority to investigate cell regulation and epigenetics (6).…”
mentioning
confidence: 99%
“…Moreover, histone PTMs cross-talk in a synergistic manner to fine-tune gene expression (5). Therefore, quantification of histone PTMs has become a high priority to investigate cell regulation and epigenetics (6).…”
mentioning
confidence: 99%
“…Strahl and Allis suggested that a "histone code" could be read by regulatory proteins and complexes [217] and many have studied the code since then [170,171,[218][219][220][221][222][223][224][225][226]. Strahl an Allis also speculated that histone PTMs could influence the modification status of other sites on the same histone or in the same nucleosome by attracting or blocking specific enzymes and it did not take long until this was shown -H2BK123-ubiquitination is for example necessary for H3K4-methylation [227] and blocking H3K14-acetylation by mutation will prevent trimethylation of H3K4 [228].…”
Section: The Histone Codementioning
confidence: 99%
“…9 Among others, new sites of acetylation, methylation, O-GlcNAcylation, crotonylation, propionylation, arginine citrullination, butyrylation, proline isomerization, malonylation, succinylation, formylation, and ADP-ribosylation have been detected and studied in a wide range of species and biological processes. [10][11][12][13][14][15][16] Serine acetylation was first reported as a chemical antagonist to phosphorylationmediated signaling pathways in eukaryotic cells, catalyzed by the Yersinia bacterial virulence factor, YopJ.…”
Section: Initial Characterization Of Histone H3 Serine 10 O-acetylationmentioning
confidence: 99%